(untitled) - Phakiti, Aek (London, 2014)
Language learning research aims to describe and fully explain how and why language learning takes place, but can fall short of its stated purpose. Systematic, rigorous research is needed if the growing field of language learning is to progress methodically. This book demonstrates and fully explains such a methodology. Given that research in language acquisition yields practical pedagogical implications, it is crucial that it is rigorous and accurate.
Luận văn tốt nghiệp
Keywords: Tiếp thu ngôn ngữ,Language acquisition